REFERRAL SYSTEM IN INDONESIA, HAS IT BEEN IMPLEMENTED CORRECTLY? - Eska Distia Permatasari, - (Community Health Society Malaysia, 2019)
Background: Policies on referral systems have long existed in Indonesia. Nonspecialistic references are still occurring and result inefficienty of health care. BPJS Kesehatan stated that there were 2.236.379 visits in the primary health care facilities referred in 2015, 214.706 visits of which were non nonspecificistic referrals. In 2016 there was an increase of 4.9 million cases of re-control compared to 2015 in secondary and tertiary outpatient, resulting in an increase in cost of 789 billion compared to 2015. This is because the referral system policy hasn’t been implement correctly. This policy brief aims to evaluate the implementation of referral system policies that exist in Indonesia. Materials and Methods: This is a policy brief with literature review approach. This policy brief was prepared by conducting literature studies on the implementation of referral systems and several health policies on referrals Result: Referral system has not been implemented properly in accordance with existing policies in Indonesia. This causes wastage costs in the implementation of universal health coverage. Implementation constraints on referral policies stem from the low knowledge of health personnel and the capacity of health care providers. Conclusion: It is appropriate to evaluate all of personel who play a role in the implementation of referral policy. Evaluation should be done from the community as the recipient of the service, health facilities as the buyer of service, the health office as the responsible implementation of referrals, as well as from the government as policy makers. Thus solutions to problems with this reference system can be applied so that the correct referral system can be realized.